2006
DOI: 10.1242/dev.02694
|View full text |Cite
|
Sign up to set email alerts
|

T-Box transcription factor Tbx20 regulates a genetic program for cranial motor neuron cell body migration

Abstract: Members of the T-box transcription factor family (Tbx) are associated with several human syndromes during embryogenesis. Nevertheless, their functions within the developing CNS remain poorly characterized. Tbx20 is expressed by migrating branchiomotor/visceromotor (BM/VM) neurons within the hindbrain during neuronal circuit formation. We examined Tbx20 function in BM/VM cells using conditional Tbx20-null mutant mice to delete the gene in neurons. Hindbrain rhombomere patterning and the initial generation of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 62 publications
0
84
1
Order By: Relevance
“…It has been confirmed that Tbx is required for proper neural crest migration and to stabilize spatial patterns during middle and inner ear development [39]. Furthermore, Tbx gene programs a variety of hindbrain motor neurons for migration, independent of directionality, and in facial neurons is a positive regulator of the non-canonical Wnt signaling pathway [40]. We conclude that Tbx controls neuronal polarity to regulate neural crest migration.…”
Section: Discussionmentioning
confidence: 61%
“…It has been confirmed that Tbx is required for proper neural crest migration and to stabilize spatial patterns during middle and inner ear development [39]. Furthermore, Tbx gene programs a variety of hindbrain motor neurons for migration, independent of directionality, and in facial neurons is a positive regulator of the non-canonical Wnt signaling pathway [40]. We conclude that Tbx controls neuronal polarity to regulate neural crest migration.…”
Section: Discussionmentioning
confidence: 61%
“…Moreover, this transcription factor is evolutionarily conserved from flies to humans, suggesting that its transcriptional regulation of Robos and Slits is a conserved mechanism (Takeuchi et al, 2005). Accordingly, both Tbx20 and Slit1/Slit2 knockout mice have defects in the development of hindbrain motoneurons (Hammond et al, 2005;Song et al, 2006). In the mouse, Tbx1 regulates a second transcription factor, Gbx2, which functions in hindbrain and pharyngeal arch artery (PAA) development (Calmont et al, 2009).…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…7I,J). Previous reports indicated that during neural plate formation in zebrafish, tbx2b expression is regulated by the Wnt receptor frizzled 7a (fzd7a) (Fong et al, 2005), and that in the developing mouse hindbrain, Tbx2 regulates expression of Wnt planar cell polarity (PCP) genes including Fzd7 (Song et al, 2006). However, we find that disrupting the Wnt PCP signaling pathway, by mutation of the proteoglycan knypek (glypican) (Topczewski et al, 2001) or van gogh-like 2 (strabismus; also known as trilobite in zebrafish) (Jessen et al, 2002), has no effect on tbx2b expression, parapineal specification or migration (see Fig.…”
Section: Research Articlementioning
confidence: 99%